2018
DOI: 10.1016/j.aott.2018.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic resection of an osteochondral loose body in the distal radioulnar joint: A case report

Abstract: We report a 34-year-old man who presented with ulnar wrist pain, painful click, and locking during forearm rotation following a motorcycle accident. Plain radiographs showed a loose body in the distal radioulnar joint (DRUJ), deformity of the sigmoid notch and ulnar head, and ulnar minus variant. The DRUJ deformity was assumed to be associated with physeal injury of the distal ulna during childhood. Conservative treatment with a splint and oral analgesics for 3 months failed. During DRUJ arthroscopy, osteoarth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 16 publications
(17 reference statements)
0
3
0
Order By: Relevance
“…Locking of the distal radioulnar joint (DRUJ) causes restriction of active and passive pronation or supination of the forearm. It is relatively rare and has been described in only a few studies that have reported the causes to be loose bodies arising from synovial osteochondromatosis (De Smet and Van Wetter, 1987; Koh et al., 2003; Ono et al., 1994; Slesarenko et al., 2004; Yano et al., 2018) or interposition of the extensor carpi ulnaris (ECU) tendon (Araki et al., 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Locking of the distal radioulnar joint (DRUJ) causes restriction of active and passive pronation or supination of the forearm. It is relatively rare and has been described in only a few studies that have reported the causes to be loose bodies arising from synovial osteochondromatosis (De Smet and Van Wetter, 1987; Koh et al., 2003; Ono et al., 1994; Slesarenko et al., 2004; Yano et al., 2018) or interposition of the extensor carpi ulnaris (ECU) tendon (Araki et al., 1994).…”
Section: Introductionmentioning
confidence: 99%
“…The radiographs of the elbow demonstrated a fracture of the humeral medial epicondyle and fracture around the radial head (►Fig. 1). It is unclear whether there was pain at the wrist at the time of injury.…”
Section: Case Reportmentioning
confidence: 99%
“…It is relatively rare; only a few case reports of locking of the DRUJ have been published. [1][2][3][4][5][6][7] Previously reported causes of DRUJ blocking include: loose bodies such as synovial osteochondromatosis, [1][2][3][4][5] interposition of the extensor carpi ulnaris tendon, 6 or the volar portion of the triangular fibrocartilage complex (TFCC) tear. 7 Bipolar injury of the forearm involves bone and soft tissue injuries to the wrist, forearm, or elbow.…”
mentioning
confidence: 99%